SMARCA5 is required for the development of granule cell neuron precursors and Sonic Hedgehog Medulloblastoma growth - Foteini Tsiami; Layla Drwesh; Surender Surender; Julia Fitzgerald; Jens Schittenhelm; David J. Picketts; Rosalind A. Segal; Ghazaleh Tabatabai; Daniel J. Merk (Scientific Reports)
Abstract Medulloblastoma constitutes a molecularly diverse group of malignant embryonal brain tumors. Sonic hedgehog molecular group of medulloblastoma (SHH-MB) is a highly heterogeneous tumor entity, characterized by constitutive activation of the SHH signaling pathway. Due to lack of suitable cell line models, little is known about genetic dependencies in SHH-MB outside of the SHH pathway. By performing a CRISPR-Cas9 dropout screen in SMB21 cells derived from SHH-MB in Ptch +/− mice, we aimed to identify genetic vulnerabilities in SHH-MB. Among the top scored gene hits, members of the SNF2-family of ATP-dependent chromatin remodelers including Smarca5 emerged as genetic dependencies in SHH-MB, and we validate that Smarca5 knockout inhibits SHH pathway activation and SHH-MB cell proliferation. Additional genetic ablation experiments in vivo revealed that conditional deletion of Smarca5 in cerebellar granule cell neuron precursors (GCNPs), the cell origin of SHH-MB, significantly reduces the proliferative capacity of GCNPs and leads to cerebellar hypoplasia in mice. Furthermore, loss of Smarca5 in GCNPs in an established mouse model of SHH-MB results in prolonged survival of tumor bearing mice. Our data underline the critical role of SMARCA5 during the development of the cerebellum and the pathogenesis of SHH-MB.